PENGARUH HUMAN RELATION DAN LINGKUNGAN KERJA FISIK TERHADAP ETOS KERJA KARYAWAN WAREHOUSE PT. TALKINDO SLAKSA ANUGRAH TANGERANG SELATAN - Iqbal, Muhammad; Susilo Wardani, Endang (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of human relations and physical work environment on employee work ethic at the Warehouse of PT Talkindo Slaksa Anugrah South Tangerang. This type of research is quantitative research. The sampling technique used saturated sampling and obtained a sample of 62 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are Human Relations has a significant effect on employee work ethic with a coefficient of determination of 37.5% and hypothesis testing obtained t count > t table or (5.994 > 1.67065). The physical work environment has a significant effect on employee work ethic with a determination coefficient of 33.4% and hypothesis testing obtained t count > t table or (5,487 > 1,67065). Human relations and the physical work environment simultaneously have a significant effect on employee work ethic with the regression equation Y = 9.404 + 0.387 X1 + 0.366 X2. The coefficient of determination is 47.1% while the remaining 52.9% is influenced by other factors. Hypothesis testing obtained F count> F table or (26.250 > 3.15).